Genetic Recourses : Evaluation Of The Value Of Some Old Latvian Flax Accessions (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In the resent years evaluation and conservation of genetic recourses becomes of great importance. Some of the genotypes could be lost when un-sufficient attention is given to them. Some old (created before WWII) Latvian flax accessions have been investigated at the collection nursery at the Upytė Experimental Station of the Lithuanian Research Centre for Agriculture and Forestry in 2007-2010. Phenological phases, plant height, flower colour, stem, seed and long fibre yield, fibre content and quality (flexibility, strength, quality number), duration of vegetation period, resistance to lodging, etc., have been investigated. The most valuable genotypes have been suggested to be used in further breeding programs.